Using discrete-time mathematical programming to optimise the extraction rate of a durable non-renewable resource with a single primary supplier - Albert Corominas (Operations Research Perspectives, 2017)
A non-linear discrete-time mathematical program model is proposed to determining the optimal extraction policy for a single primary supplier of a durable non-renewable resource, such as gemstones or some metals. Karush, Kuhn and Tucker conditions allow obtaining analytic solutions and general properties of them in some specific settings. Moreover, provided that the objective function (i.e., the discounted value of the incomes throughout the planning horizon) is concave, the model can be easily solved, even using standard commercial solver. However, the analysis of the solutions obtained for different assumptions of the values of the parameters show that the optimal extraction policies and the corresponding prices do not exhibit a general shape.
Keywords: 330; Durable non-renewable resources; Single primary supplier; Non-linear programming